La memoria ‘estesa’ della moda. Come valorizzare l’heritage aziendale con la tecnologia - Pompa, Chiara (ZoneModa Journal, 2020)
During the past months of lockdown and social distancing, necessary to counter the spread of the COVID-19 pandemic, the fashion world opened the doors of its digital databases, sharing the cultural heritage with the web community. A praiseworthy initiative capable of stimulating a reflection on the dimension of accessibility to fashion archives, as well as on the uses that can be made of their materials. This phenomenon is in fact observable from multiple perspectives: if on the one hand, it may provide useful insight into the progress of digitalization, on the other it underlines the limited use of Extended Reality in corporate archives and museums of Fashion System, that has adopted this technology primarily in both B2B and B2C retail. Starting from the analysis of the state of the art, the paper aims to trace potential paths for future research on this field, in order to support the fruition and valorization of the fashion heritage through augmented and virtual reality technologies.